A HUMANISTIC APPROACH TO ADULT EDUCATION: LEARNING FROM THE INSIDE OUT - Alyce Cooks, Darwyn Hackney, Sanetta George Jackson (2002)
We approach the adult educator/adult learner relationship from an affective perspective, noting the role of diversity, as we establish parameters for this paper. One of us has stated that a dear friend and adult educator told her many times that more is "caught than taught" (referring to informal and incidental learning that takes place on a daily basis and in most situations). We believe the truth of that axiom is applicable to all interactions between adult educators and adult students. It is essentially, and in the final analysis, a human relationship. We will examine diversity as it relates to teacher-learner interaction specifically in four areas that impact this humanistic educational process: (1) adult educator/adult student interpersonal relationships as they apply to the instructional process; (2) the effect of spirituality on the adult ducator/adult student relationship; (3) interaction between the adult educator and adult student in a counseling setting, and finally; (4) the effectiveness of adult educators in evaluating programs for a diverse adult student population.